Book review: Chaitanya Ravi, A Debate to Remember-––The US–India Nuclear Deal. (September 2019) - Gogoi, Yuvaraj
Chaitanya Ravi, A Debate to Remember-––The US–India Nuclear Deal . New Delhi: Oxford University Press, 2018, 309 pp., ₹995, ISBN-13: 978-0-19-948170-5 (Hardcover) .